PENINGKATAN HASIL BELAJAR DENGAN MEDIA PEMBELAJARAN KAHOOT PADA PESERTA DIDIK KELAS VIII B SMP NEGERI 15 SEMARANG - Fahrul Iqwan (Sosiolium: Jurnal Pembelajaran IPS, 2024)
Teachers as managers of learning activities have a great responsibility because teachers have a great influence on the process and achievement or learning outcomes. The problems encountered by class VIII B students are related to less conducive classroom conditions, lack of interest in learning, and low student learning outcomes. This study aims to determine the improvement of student learning outcomes by using kahoot learning media on conflict and integration materials. The research method used is classroom action research which is carried out in two cycles. The subjects in this study were 34 students of grade VIII B SMP N 15 Semarang. Data collection tools use observation sheets and tests. The analysis technique is descriptive analysis using N-Gain. The results showed that social studies learning on conflict material and integration with kahoot media can improve student learning outcomes with pre-test and post-test scores that increase in each cycle